THE IMPLEMENTATION OF DISCIPLINE CHARACTER VALUES IN GROWING INDEPENDENT LEARNING DURING THE PANDEMIC COVID-19 - Azizatul Alif Syafriza (Indonesian Journal of Elementary Teachers Education, 2021)
The main purpose of this research is to describe the invest of disciplined character in an effort to grow independent learning. This research activity was carried out through an in-depth study with a qualitative descriptive approach at random at the elementary school in the Yogyakarta. The data collection technique was done by triangulation (combined), using inductive/qualitative data analysis. Triangulation of data was carried out by means of interviews, observations, and documents related to the invest of character values in growing independent learning during the pandemic. Interviews were conducted with randomly selected primary school teachers and randomly selected 4th and 5th grade students from several schools. Observations were made by following the virtual learning process conducted by the interviewed teachers. Supporting documents used are student attendance data and recap of assignments for a certain period. The data obtained in the field is recorded in descriptive form as it is in the form of small notes then a reflection note is made containing comments from researchers related to phenomena in the field. From the results of interviews with teachers and parents obtained data that the character of discipline will affect the growth of various independent characters in students. Students who have a disciplined character will get used to living regularly. Awareness will grow in students to carry out their activities because students feel the need to do so. Independent learning during online learning requires cooperation between teachers and parents or guardians. Students remain under parental supervision when outside the virtual learning process. Parents or guardians play a role as mentors for students in growing independent learning. The character of discipline and independence that needs to be instilled in students is not only limited to learning. But also discipline in carrying out their daily routines. This independence of learning in students will have an impact on reducing the dependence of students to learn by waiting for orders or accompanied by parents.